2017
DOI: 10.4236/jbcpr.2017.52004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Urban Noise and the Health of Users of Public Spaces—A Case Study in Vitoria, ES, Brazil

Abstract: Urban populations today are exposed to high levels of noise, which may cause discomfort and lead to health problems. Most of these noises are traffic-generated; therefore, this study focuses on evaluating the soundscapes of urban open spaces to determine its importance for the health of the citizen, since such spaces can function as noise attenuators. The methodology of this study involved a literature review, computer simulations and interviews with users of the aforementioned open spaces. The case study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
4
10
0
Order By: Relevance
“…In the two areas under study, the most frequent complaints about the effects of urban noise were irritability and poor concentration (Figure 10). These results are comparable to those found by Paneto et al [11], which addressed the theme "Relationship between urban noise and the health of users of public spaces…." Paneto et al [11] applied a questionnaire to 375 people, and the main reactions to noise exposure were as follows: irritability (58%), difficulty to concentrate (42%), sleeping disorders (20%) and headaches (20%).…”
Section: Resultssupporting
confidence: 88%
“…In the two areas under study, the most frequent complaints about the effects of urban noise were irritability and poor concentration (Figure 10). These results are comparable to those found by Paneto et al [11], which addressed the theme "Relationship between urban noise and the health of users of public spaces…." Paneto et al [11] applied a questionnaire to 375 people, and the main reactions to noise exposure were as follows: irritability (58%), difficulty to concentrate (42%), sleeping disorders (20%) and headaches (20%).…”
Section: Resultssupporting
confidence: 88%
“…Reference [2] points out that "The acoustic quality of a city depends not only on the absence of noise but also on the presence of quietness and liveliness." Similarly, in [3] discuss "The importance of public spaces in lowering urban traffic noise. Acoustic simulations indicated that traffic-related noise is dissipated in open spaces, such as public squares."…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic simulations indicated that traffic-related noise is dissipated in open spaces, such as public squares." Moreover, according to [3], public parks are places of quietness and well-being for urban populations. Reference [2] also emphasize that the question is not whether a city is noisy or not, but rather whether its residents have access to quiet spaces, i.e., a quiet house and neighborhood, as well as quiet urban spaces.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations